A CLINICAL STUDY ON THE EFFECT OF VIRECANA KARMA WITH TRIVRUTADI MODAKA IN THE MANAGEMENT OF TAMAKA SVASA (BRONCHIAL ASTHMA) - Rama Devi, Jayavarapu; Sreenivasulu, Y.; Sadanandam, Ch. (International Journal of Ayurveda and Pharma Research, 2015)
Tamaka svasa is a Vatakaphaja vyadhi, originating from Pittasthana and manifested through Pranavaha Srotas. Vata get obstructed by Kapha dosha and travels into Pratiloma gati (opposite direction) and in turn causes Svasa (Dyspnoea). Its clinical features resembles with Bronchial asthma. Objectives: The study was carried out to assess the role of Virecana karma in the management of Tamaka svasa with Trivrutadi Modaka. Materials and methods: The clinical study was conducted at Dr.B.R.K.R.Govt. Ayurvedic Hospital and Research Centre, Erragadda, Hyderabad. 30 patients of either sex fulfilling the clinical criteria for diagnosis of Tamaka svasa (bronchial asthma) were selected in accordance with following inclusion & exclusion criteria. Murchita Tilataila was given for Snehapana and the Virecana yoga was Trivrutadi Modaka. The result was assessed at every 15 days. Subjective and objective parameters were analyzed before and after the treatment. Results: There was moderate relief in 23 Patients (76.66%), Marked relief in 4 Patients (13.33%) and 3 Patients (10.00%) showed mild relief, Complete remission was not found. Conclusion: Virecana karma (Purgative Therapy) has given maximum effect to pacify the almost entire range of signs and symptoms associated with the disease and by reducing its frequency, severity, emergency drug usage and there by providing quality life to the patients.